2022
DOI: 10.3389/fpubh.2022.941183
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of 3-year inpatient TB cases in Zunyi, China: Increased TB burden but improved bacteriological diagnosis

Abstract: BackgroundAs one of the top three high tuberculosis (TB) burden countries, China is a country where the overall TB incidence continues to decline. However, due to its large population and area, the increased TB burden exists in regional areas.MethodsThis retrospective study analyzed local inpatient pulmonary TB cases in the Affiliated Hospital of Zunyi Medical University (AHZMU) from January 2016 to December 2018 in a high TB incidence and economically-less-developed area of China. Four methods, acid-fast baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The participants were aged 18-84 years old, the male to female ratio is ~1.45:1. Pulmonary TB was confirmed according to the diagnostic criteria of pulmonary TB in the health industry standards of China (WS 288-2008 and WS 288-2017) ( 30 ): i) nucleic acid test shows a positive result for M. tuberculosis and ii) chest radiological imaging shows typical clinical symptoms of active TB infection. HIV infection was confirmed according to the diagnostic criteria based on the Chinese Guidelines for Diagnosis and Treatment of HIV/AIDS (2018) ( 31 ): Nucleic acid test shows a positive result for HIV.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were aged 18-84 years old, the male to female ratio is ~1.45:1. Pulmonary TB was confirmed according to the diagnostic criteria of pulmonary TB in the health industry standards of China (WS 288-2008 and WS 288-2017) ( 30 ): i) nucleic acid test shows a positive result for M. tuberculosis and ii) chest radiological imaging shows typical clinical symptoms of active TB infection. HIV infection was confirmed according to the diagnostic criteria based on the Chinese Guidelines for Diagnosis and Treatment of HIV/AIDS (2018) ( 31 ): Nucleic acid test shows a positive result for HIV.…”
Section: Methodsmentioning
confidence: 99%
“…11 Since this survey, China has made a concerted effort to improve the control of drug-resistant TB. Although the trends in the prevalence of drugresistant TB have been evaluated in several individual regions of China, including Beijing, Zhejiang, Henan, and Guizhou, [12][13][14][15][16][17] most of these studies were based on hospitalized TB patients and therefore the reported prevalence of drug resistance may have been higher than would be found in population-based studies.…”
Section: Introductionmentioning
confidence: 99%